Critical writing in higher education: A need analysis survey - Nugroho, Arif; Putro, Nur Hidayanto Pancoro Setyo; Syamsi, Kastam (UIN Raden Mas Said Surakarta, 2024)
Critical thinking and writing are considered as one of the twenty-first century skills that must be acquired by students; however, research on this area still needs more empirical paucity of evidence. The present study aims to reveal English students’ learning needs on critical writing course at university level. Drawing on survey research, this study invites 437 undergraduate students majoring in English department from four universities in Surakarta municipality, Indonesia. Statistical analysis identifies key student priorities: acquiring, evaluating, and synthesizing information; effective communication; articulating their opinions; publishing their writings; and presenting materials at international forums. The data also reveal that English students encounter significant challenges in critically analyzing information and drawing conclusions from reading passages. Regarding their expectations for critical writing instruction, students aspire to enhance both their critical thinking and academic writing abilities. This is particularly pertinent for pre-service teachers who will need to teach content and produce both academic and non-academic publications. Additionally, the survey indicates a positive student response to incorporating technology (e.g., social media, networking sites, websites) into collaborative learning activities for critical writing courses. These findings provide valuable insights into the needs and expectations of English students regarding critical writing courses, offering a clear direction for course design and instructional strategies.